The Implementation of Technology in Physical Education Learning for Elementary School Students: Challenges and Opportunities - Elbadiansyah, Elbadiansyah; Aziz, Aulia Luqman; Sain, Zohaib Hassan; Lawal, Uthman Shehu (Lembaga Yasin AlSys, 2025)
The implementation of technology in physical education learning at elementary schools is an innovative step to enhance the effectiveness and efficiency of the learning process. Technology offers broader accessibility, increases student engagement, and supports the development of digital skills. However, its implementation faces various challenges, such as technological disparities, resistance to change, limited resources, data security issues, and the potential for over-reliance on technology. With support from the government, schools, and communities, technology can be integrated in a balanced manner, serving as a supporting tool to achieve the goals of physical education without compromising its essence.